Investigating solvent effects on the magnetic properties of molybdate ions (MoO42−) with relativistic embedding. Issue 21 (10th March 2020) - Halbert, Loïc; Olejniczak, Małgorzata; Vallet, Valérie; Severo Pereira Gomes, André
Abstract: We investigate the ability of mechanical and electronic density functional theory‐based embedding approaches to describe the solvent effects on nuclear magnetic resonance (NMR) shielding constants of the 95 Mo nucleus in the molybdate ion in aqueous solution. From the description obtained from calculations with two‐ and four‐component relativistic Hamiltonians, we find that, for such systems, spin‐orbit coupling effects are clearly important for absolute shielding values, but for relative quantities, a scalar relativistic treatment provides sufficient estimation of the solvent effects. We find that the electronic contributions to the solvent effects are relatively modest yet decisive to provide a more accurate magnetic response of the system when compared to reference supermolecular calculations. We analyze the errors in the embedding calculations by statistical methods, as well as through a real‐space representation of NMR shielding densities, which are shown to provide a clear picture of the physical processes at play. Abstract : A relativistic quantum embedding approach based on frozen density embedding can efficiently and reliably represent solvation effects on nuclear magnetic resonance shielding constants of the 95 Mo nucleus. In order to understand solvation effects, real‐space representations of shielding densities, instead of electron densities, should be analyzed.